Planning Law and Accessibility: Third Party Permit Appeals by Persons with Disabilities - Chipeur, Stephanie (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
A physical obstacle, such as a step at the entrance of a building, is the product of the interplay of regulations that govern what and we build. The human rights complaint process can provide a remedy to people with disabilities when they are excluded from public spaces. But there are limits to what can be accomplished by way of a human rights complaint. Human rights commissions and tribunals are not competent to mediate or adjudicate complaints about accessibility before construction commences, because any alleged discrimination is only hypothetical. But just because human rights law is limited in this way should not mean that people with disabilities must wait to encounter inaccessibility before they can influence what and how we build. Planning law legislation in Canada mandates public consultation and it also gives members of the public the right to contest planning decisions by way of an appeal. For people with disabilities, this would mean challenging development and building permits that have already been issued if the proposed development is not accessible.After a municipality issues a development permit, most jurisdictions in Canada allow for an appeal by a third party. There are also some jurisdictions that also allow for this type of appeal after the municipality issues a building permit. If successful in an appeal, members of the public who are opposed to a project, or some of its aspects, may block construction altogether or require modifications. These appeal processes could offer an opportunity for people with disabilities to have a direct impact on how we construct the built environment. An appeal at the permit stage is a promising complement to a human rights complaint, because it is prospective rather than retroactive.